Differences in activation patterns of the hamstring muscles during sprinting - Higashihara, A.; Ono, T.; Fukubayashi, T. (Sports injuries and prevention, 2015)
In this chapter, we evaluate the functional characteristics of the hamstring muscles during sprinting. During near maximal sprinting speed, the respective hamstring muscles exhibited very different characteristics of electromyographic (EMG) activation within the sprinting gait cycle. The activation demand of the BFlh muscles is high before and after foot contact due to their function as hip extensors, while the ST muscle shows high activation primarily during the control of knee extension and hip flexion in the mid-swing phase. The mechanism underlying these activation characteristics may involve architectural differences between the hamstring muscles, which likely reflect each muscle`s function during sprinting. A complex neuromuscular coordination pattern of the hamstring muscles during sprinting is accomplished by the utilisation and activation of each muscle`s specific functional differences.